Antioxidant Property and Health Benefits of Grape Byproducts - Bhise, Suresh; Kaur, A; Gandhi, Neeraj; Gupta , Rahul (Journal of Postharvest Technology, 2024)
Grape skin and seeds, produced by the winemaking industry, are  increasingly used to obtain functional food ingredients. Grape  seed is a better source of antioxidative constituents than skins of  grape/wine byproducts. Functional ingredients of grape seed  include several flavonoids with a phenolic nature such as  monomeric flavanols, dimeric, trimeric, and polymeric  procyanidins, and phenolic acids. The antioxidant activity of  grape seed phenolic compounds is closely associated with  activity against various types of cancer as well as cardiovascular  and other dermal disorders. Grape seed has antioxidant,  antiallergenic, antihistamine, anti-inflammatory and immune  boosting properties and it helps the body against allergens and  carcinogens. Grape seed extract is frequently recommended to  combat macular degeneration, cataracts, and eyestrain. The  present review article discusses the functional characteristics of  grape pomace and their health benefits against several human  diseases and disorders.
Keywords: Grape; Antioxidant; Phenolic compound Seed; Pomace; Byproducts